1995
DOI: 10.1080/02791072.1995.10472467
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Spouses of Substance Abusers in Treatment: Gender Differences

Abstract: Studies exploring gender differences among substance abusers in treatment have been fairly consistent in finding that females who enter treatment express more severe psychological and psychosocial disturbances than males, despite presenting with shorter and less intense substance abuse histories. However, strands of evidence suggest that the presence of a spouse, generally perceived as an asset in the treatment of the substance abuser, may have different implications for females than for males. In order to cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Three of the nine included studies were conducted in Australia [ 33 35 ]. The remaining studies originated from Canada [ 36 ], New Zealand [ 37 ], the Netherlands [ 30 ], USA [ 8 ], Croatia [ 29 ], and Spain [ 38 ]. The studies were spread over a wide timeframe, with two studies published before 2000 [ 35 , 36 ] and seven published after 2010.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the nine included studies were conducted in Australia [ 33 35 ]. The remaining studies originated from Canada [ 36 ], New Zealand [ 37 ], the Netherlands [ 30 ], USA [ 8 ], Croatia [ 29 ], and Spain [ 38 ]. The studies were spread over a wide timeframe, with two studies published before 2000 [ 35 , 36 ] and seven published after 2010.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of the studies aimed to examine the impact of SUPs on close family members, with QoL as one of the primary outcomes. In four of the studies, the participants were recruited when their partner was in treatment [ 29 , 30 , 36 , 38 ], in one study the participants were recruited through newspaper advertisements [ 35 ], and in one study the participants were recruited in mutual aid support groups (Al-Anon Family Groups and FDH, a program of the Self-Help Addiction Resource Centre (SHARC), both in Australia) [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…While there are a growing number of studies on the gender differences of substance users seeking treatment. [ 20 - 23 ] and in treatment settings [ 24 , 25 ], little attention has been given to the experience and complex treatment needs of drug-using couples.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, statistics showed that the loved ones of individuals who abused alcohol or drugs experienced numerous stressors as a result, including domestic violence, financial problems, marital difficulties, and social embarrassment or isolation (Romijn, Platt, Schippers, & Schaap, 1992;Velleman et al, 1993). Not surprisingly, these CSOs frequently suffered from depression, anxiety, physical illness, and low self-esteem (Brown, Kokin, Seraganian, & Shields, 1995;Spear & Mason, 1991).…”
Section: Community Reinforcement and Family Training (Craft) Backgroundmentioning
confidence: 99%